2017
DOI: 10.1016/j.cytogfr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between insulin-like growth factor (IGF) receptor and integrins through direct integrin binding to IGF1

Abstract: It has been generally accepted that integrin cell adhesion receptors are involved in growth factor signaling (integrin-growth factor crosstalk), since antagonists to integrins often suppress growth factor signaling. Partly because integrins have been originally identified as cell adhesion receptors to extracellular matrix (ECM) proteins, current models of the crosstalk between IGF1 and integrins propose that ECM ligands (e.g., vitronectin) bind to integrins and IGF1 binds to IGF receptor type 1 (IGF1R), and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Integrin receptors are also involved in growth factor signaling. Studies have shown that integrin aVβ3 plays a critical role in IGF1R signaling by binding directly to IGF [53]. Therefore, integrin antagonists can suppress growth factor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin receptors are also involved in growth factor signaling. Studies have shown that integrin aVβ3 plays a critical role in IGF1R signaling by binding directly to IGF [53]. Therefore, integrin antagonists can suppress growth factor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, after pressure overload, isolated cardiac fibroblasts display changes in adhesion, migration, and collagen gel contraction, which are all dependent on integrin β1 activity 8 . Integrins can modulate intracellular signaling directly or coordinately with many growth factor receptors, including epidermal growth factor receptors (EGFR), insulin receptor, and platelet derived growth factor receptor (PDGFR) 10,12‐15 . In fact, positive crosstalk allows integrins to amplify growth factor receptor signaling by either receptor phosphorylation or direct physical interaction 10,12‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several integrins, including ανβ3 and α6β4 are overexpressed in human cancers [ 2 ]. We have reported that integrins crosstalk with growth factors through direct binding to growth factors [e.g., fibroblast growth factor-1 (FGF1) [ 3 ], insulin-like growth factor 1 (IGF1) [ 4 6 ], neuregulin-1 [ 7 ], fractalkine [ 8 ]] and subsequent ternary complex formation with cognate receptor [e.g., integrin/IGF1/insulin-like growth factor type 1 receptor (IGF1R)] [ 9 , 10 ]. We describe this as the ternary complex model of growth factor signaling.…”
Section: Introductionmentioning
confidence: 99%